2021
DOI: 10.1007/s11082-021-03124-2
|View full text |Cite
|
Sign up to set email alerts
|

Security and communication distance improvement in decoy states based quantum key distribution using pseudo-random bases choice for photon polarization measurement

Abstract: This paper proposes a new quantum key distribution(QKD) protocol, namely the pseudo-random bases entangled photon based QKD (PRB-EPQKD) protocol. The latest mainly focuses on three properties, including the security of the protocol, the secure key size and the maximum communication distance between legitimate communication users (Alice and Bob). To achieve this, we first consider a spontaneous-parametric-down (SPDC) photon source located in a low-earth-orbit (LEO) type satellite capable of producing and distri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Long-distance non-locality, extended coherence storage [22], and the rebirth of entangled states have become important research focuses around the world to have practical value for quantum computing and communication [23,24]. Quantum entanglement has its applications in many fields, specifically to explain quantum communication protocols, such as quantum cryptography [25,26], quantum-coding [27], quantum computing algorithms [28], and quantum state teleportation [29]. The entanglement between two parties drenched in an environment was firstly found theoretically and it was shown that it can disappear in infinite time.…”
Section: Introductionmentioning
confidence: 99%
“…Long-distance non-locality, extended coherence storage [22], and the rebirth of entangled states have become important research focuses around the world to have practical value for quantum computing and communication [23,24]. Quantum entanglement has its applications in many fields, specifically to explain quantum communication protocols, such as quantum cryptography [25,26], quantum-coding [27], quantum computing algorithms [28], and quantum state teleportation [29]. The entanglement between two parties drenched in an environment was firstly found theoretically and it was shown that it can disappear in infinite time.…”
Section: Introductionmentioning
confidence: 99%